Isotropic Spin Trap EPR Spectra Simulation by Fast Fourier Transform (FFT) - S. Laachir; M. Moussetad; R. Adhiri; A. Fahli (E-Journal of Chemistry)
The detection and investigation of free radicals forming in living systems became possible due to the introduction of the method of spin traps. In this work, the electron spin resonance (ESR) spectra of DMPO/HO. and MGD-Fe-NO adducts are reproduced by simulation, based on the Fast Fourier Transform (FFT). The calculated spectral parameters as the hyperfine coupling constants, agree reasonably with the experimental data and the results are discussed.